Mapping unmarked graves with Ground Penetrating Radar at the Walkerville Wesleyan Cemetery, Adelaide. Issue 1 (15th July 2020) - Moffat, Ian; Linsell, John; Vella, Anthea; Duke, Belinda; Kowlessar, Jarrad; Griffith, John Gareth; Down, Allison
Abstract: A Ground Penetrating Radar (GPR) survey was undertaken to map unmarked graves within the historic Walkerville Wesleyan Cemetery in Adelaide. The survey revealed 168 probable graves, 20 possible graves and 68 additional graves containing more than one interment. Our results demonstrate the utility of geophysical methods, specifically GPR, as a non-invasive tool for managing the cultural heritage of cemetery sites and suggest that this method could play a more significant role in Australian archaeology.